A database on genes increasing resistance of wheat and relative species against pathogenic fungi - O. G. Smirnova; A. V. Kochetov (Вавиловский журнал генетики и селекции)
Fungi belong to the major plant pathogens and investigation of plant resistance genes is a quite important task. During the last years many wheat resistance genes were identified. However, the sequencing of the Triticum aestivum L. genome is still going on and the nucleotide sequences of most resistance genes are not yet known. In addition, the study of allelic variants of resistance genes is important for better understanding of the molecular mechanisms of their action. In this paper we present an information resource for accumulation of data on sequenced genes of wheat and its relatives providing resistance against diseases caused by fungal pathogens. The database (Pathogenesis-Related Genes, PRG) contains information on gene chromosomal localizations and functional activities, nucleotide sequences and single nucleotide polymorphisms associated with their effects. PRG provides data on the proteins encoded, pathogens and diseases, as well as on the resistance gene expression patterns in response to pathogen inoculations, exposure to hormones and various external stimuli. It also has cross-references with related entries from the databases on nucleotide sequences (GenBank) and proteins (UniProt). Information entered into the database is a result of the annotation of scientific publications and manual curation. Currently PRG compiles data on 75 allelic variants of 66 resistance genes. The PRG database was developed on the basis of the SRS (Sequence Retrieval System) platform. This system allows the use of complex queries and visualization tools and automatically generates www-interface with the information in table or text formats. PRG may be useful for researchers studying plant biology or breeding new plant cultivars resistant to fungal diseases. It is available at the address: http://srs6.bionet.nsc.ru/srs6bin/cgi-bin/wgetz?-page+top+-newId.